METHODOLOGIES FOR THE USE OF ELECTRONIC TESTING - Natalia LUPAȘCO; Dorina CUȘNIR (Acta et Commentationes, Sciences of Education, 2019)
Assessment in education is delicate due to the impact it has on the pupils. Currently, in orderto maintain the dynamics and the attractiveness of teaching-learning activities in the field of education,innovative computer-assisted assessment methods are being used increasingly innovative methods forevaluating computer-assisted, which refers to the use of information and communication technologies,media for the distribution of didactic materials and training skills for students to achieve the highestresults in the assessment of the school.